A Major Uplift: Recent Developments in REGION - Rowe, Francisco (REGION, 2022)
This editorial describes improvements REGION implemented in the first months of 2022. Although they are not directly visible to authors or readers, they are important for the quality of the journal and for the visibility of the articles published in REGION.